Interview with Luca Fonnesu - Fonnesu, Luca; Sandra V. (Con-Textos Kantianos. International Journal of Philosophy, 2026)
Interview with Luca Fonnesu, conducted by Sandra V. Palermo, in which the Italian philosopher discusses how his philosophical research has evolved since his university days, what the philosophical and political climate was like during his formative years, and how his philosophical interests intersected with Kantian thought. The interview also discusses Kant’s importance for contemporary moral philosophy and epistemology, the role of philosophical societies and the relationship between philosophy and history of philosophy.